The effects of systemic α1-adrenoreceptor antagonists on pupil diameter. Issue 4 (22nd October 2011) - Cooney, Theresa M; Wu, Albert; Wilkes, Geoffrey; Finkelstein, Jerome I; Musch, David C
Abstract : Aim: To assess differences in pupil diameter between men taking systemic α1 -adrenoreceptor antagonists and controls. Setting: University of Michigan clinics, USA. Methods: Male patients over the age of 50 years were recruited from clinics over 3 months and divided into two groups: 18 study patients taking α1 -adrenoreceptor antagonists (Flomax, Uroxatral, Cardura and Hytrin) and 31 control patients who had never been on them. Those with conditions known to affect pupil diameter were excluded. Pre-dilation pupil diameters were recorded using a pupillometer in mesopic and scotopic conditions. Right eyes were dilated with phenylephrine and tropicamide, and the left eye served as an undilated control. Following dilation, pupil diameters were measured in both lighting conditions. Results: No statistically significant difference was found in pupil mydriasis of patients taking α1 -antagonists versus controls (mesopic p=0.37, scotopic p=0.67). When considering only those patients taking tamsulosin, the lack of significance remained. The duration of time on the medication did not have a statistically significant effect on pupil mydriasis. Comparison of pupil diameters of patients on tamsulosin with those on non-selective α1 -antagonists, both before and after dilation, showed no significant difference in pupil mydriasis (mesopic p=0.77, scotopic p=1.00). Conclusions: The outcomes of this study present an interesting contrast to current literature. Previously, it had been hypothesised that a majority of patients taking α1 -antagonists would experience preoperative impairment of pupil dilation. The authors found no significant decrease in pupil diameters of patients on α1 -adrenoreceptor antagonists compared with controls, and no indication that duration or medication subtype had an effect.